Metafora Korupsi dalam Bahasa Indonesia di Portal Berita Daring - Amir, Johar; Anwar, Alifia Afdani; Saleh, Muh. (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
The purpose of this study is to describe: (1) categorization of corruption metaphors in Indonesian on online news portals, (2) conceptual mapping of corruption metaphors in Indonesian on online news portals. This type of research is qualitative research. Researchers categorize metaphors using embodiment theory, which is the theory of uniting physical experience with human cognition proposed by Lakoff and Johnson. The results of the study show that there are seven categories of corruption metaphors in Indonesian on online news portals. The seven categorizations are corruption as a journey, corruption as a power, corruption as food, corruption as an enemy, corruption as a plant, corruption as a disease, and corruption as an object. In addition to these categories, there are also subcategories of corruption as power, namely corruption as natural power and corruption as psychological power. Then, it was also found that there were also subcategories of corruption as objects, namely corruption as a building and corruption as a tool, conceptual mapping of corruption metaphors in Indonesian ahasa on online news portals has been carried out in the categories of corruption as a journey, corruption as a force with subcategories of natural power and psychological power, corruption as food, corruption as an enemy, corruption as a plant, corruption as a disease, and corruption as an object with a subcategory of buildings and tools. All of these categories have been equipped with a conceptual mapping model which is shown by the semantic characteristics mapped between the target domain and the source domain along with explanations.